Neue Zeiten - altes Recht die Anwendung von NS-Gesetzen durch deutsche Gerichte nach 1945 - Löhnig, Martin 1971- (Zeitgeschichte im Gespräch, 2017)
"While the Allied Control Council repealed many German laws passed under Nazi rule, the majority of such laws remained in force. After 1945, German courts faced the task of applying legal norms from the Nazi period under fundamentally altered conditions. This study describes the ways they dealt with this challenge using the examples of family and labor law"--